Long-Term Mortality, Healthcare Use, and Costs Associated with Sepsis: A Population-Based Retrospective Cohort Study - Farrah, Kelly (Université d'Ottawa / University of Ottawa, 2020)
The mortality and cost burden of sepsis in-hospital is high, however, there is limited information on long-term outcomes for sepsis patients post-discharge. This thesis examines the long-term mortality and healthcare costs associated with sepsis. A population-based retrospective cohort study was conducted using Ontario health administrative data. Cases, including sepsis patients with organ dysfunction (severe), and without (non-severe) were identified using a validated algorithm. Sepsis cases and non-sepsis hospital controls were matched 1:1 based on propensity score, age, sex, admission type, and admission date. Regression methods were used to adjust for remaining confounders. The thesis presents data on long-term mortality and rehospitalizations in sepsis patients compared to matched controls. The thesis also examines hospital length of stay and long-term incremental healthcare costs of sepsis. Overall the thesis indicates that the mortality and cost burden of severe sepsis exceeds those of matched controls at 1-year and up to 5-years following index hospitalization.
Keywords: sepsis; mortality; healthcare cost; hospital readmission; Ontario